2011
DOI: 10.1371/journal.pone.0019531
|View full text |Cite
|
Sign up to set email alerts
|

Premating Reproductive Barriers between Hybridising Cricket Species Differing in Their Degree of Polyandry

Abstract: Understanding speciation hinges on understanding how reproductive barriers arise between incompletely isolated populations. Despite their crucial role in speciation, prezygotic barriers are relatively poorly understood and hard to predict. We use two closely related cricket species, Gryllus bimaculatus and G. campestris, to experimentally investigate premating barriers during three sequential mate choice steps. Furthermore, we experimentally show a significant difference in polyandry levels between the two spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…The latter species' range in Europe is mainly restricted to the Mediterranean coastal regions. Both species share common life histories, utilizing similar habitats and have recently been studied for patterns of reproductive barrier development that may have caused their speciation and prevent hybridization Veen et al, 2011Veen et al, , 2013. Contact zones between these two fi eld cricket species exist in south-eastern Spain and probably also in Italy and further east, although geographical barriers like the Cantabrian Mountains probably prevent secondary contact (Bazyluk & Liana, 2000;Veen et al, 2013 and references therein).…”
Section: Samplingmentioning
confidence: 99%
See 4 more Smart Citations
“…The latter species' range in Europe is mainly restricted to the Mediterranean coastal regions. Both species share common life histories, utilizing similar habitats and have recently been studied for patterns of reproductive barrier development that may have caused their speciation and prevent hybridization Veen et al, 2011Veen et al, , 2013. Contact zones between these two fi eld cricket species exist in south-eastern Spain and probably also in Italy and further east, although geographical barriers like the Cantabrian Mountains probably prevent secondary contact (Bazyluk & Liana, 2000;Veen et al, 2013 and references therein).…”
Section: Samplingmentioning
confidence: 99%
“…Contact zones between these two fi eld cricket species exist in south-eastern Spain and probably also in Italy and further east, although geographical barriers like the Cantabrian Mountains probably prevent secondary contact (Bazyluk & Liana, 2000;Veen et al, 2013 and references therein). In contact zones of the two species, the possibility of introgression exists, and it has indeed been experimentally demonstrated that they can hybridize (Veen et al, 2011Tyler et al, 2013). The intensity of inter-specifi c crossing in the natural environment remains unknown, though earlier studies suggest that gene fl ow between these two species ought to be highly restricted via multiple reproductive barriers .…”
Section: Samplingmentioning
confidence: 99%
See 3 more Smart Citations